PENGARUH PENAMBAHAN PASTA BUAH KURMA SUKARI TERHADAP SIFAT ORGANOLEPTIK, NILAI GIZI DAN DAYA TERIMA ES KRIM SULE SUKARI SEBAGAI ALTERNATIF MAKANAN SELINGAN PADA ANAK USIA SEKOLAH DASAR - Yuliana, Lale Dwi Ayu; Darawati, Made; Salam, Abdul; Widiada, I Gde Narda (Pusat Unggulan IPTEK Poltekkes Kemenkes Malang, 2022)
Malnutrition in children can have a bad impact because in addition to increasing the risk of various diseases, it also tends to inhibit the growth and development of children. Various efforts to overcome the problem of malnutrition in children include providing food that contains high energy and protein, which can be obtained from Sule Sukari ice cream made from soy milk with the addition of Sukari Dates paste which is high in energy and protein. This research was conducted at the Food Science Laboratory, Department of Nutrition, Poltekkes Mataram in December 2021 using an experimental method with a completely randomized design (CRD) with one factor, namely the addition of Sukari date fruit paste consisting of 5 treatment levels (0%, 10%, 20%, 30%, 40%), 3 repetitions each. Organoleptic trait data were collected by hedonic organoleptic test and statistically processed using Analysis Of Variance (One Way Annova) at 95% confidence level (? = 0.05). Acceptability data was obtained through the acceptance test for elementary school-aged children in grades 4, 5 and 6 at SDN Bejelo, while nutrient data was obtained through a proximate test conducted at the Laboratory of Analytical Chemistry, University of Mataram. The addition of Sukari date fruit paste had a significant effect on the organoleptic properties, namely the color, taste and texture of Sule Sukari ice cream (p<0.05). Based on the organoleptic test, t3(20%) was the most preferred treatment by the panelists. The proximate test results showed that the selected Sule Sukari ice cream had a moisture content of 62.64%, ash content 0.84%, fat content 10.01%, protein content 3.70% and carbohydrates 22.81%. In the acceptance test, there were 30 people (93.7%) categorized as good acceptance and 2 people (6.3%) from 32 children. Sule Sukari ice cream was given as much as 135 g with energy content of 264.7 kcal, 5 g protein, 13.5 g fat, and 30.8 g KH.